Risk of diabetic ketoacidosis caused by sodium glucose cotransporter-2 inhibitors in patients with type 1 diabetes: a systematic review and network meta-analysis of randomized controlled trials - Liu, Ying; Yang, Shiwen; Jiang, Aidou; Zou, Dan; Chen, Zhaoyang; Su, Na (Frontiers in Endocrinology, 2025)
BackgroundThe benefits of sodium-glucose-cotransporter-2 (SGLT2) inhibitors in the treatment of type 1 diabetes mellitus (T1DM) have been demonstrated, but the occurrence of diabetic ketoacidosis (DKA) limits their use. The risk of DKA associated with different doses of SGLT2 inhibitous in the treatment of T1DM is unknown. We conducted a network meta-analysis to evaluate the incidence of DKA at different doses in the treatment of T1DM.MethodsWe searched electronic databases and clinical trial registries, including PubMed, Embase (Ovid SP), the Cochrane Central Register of Controlled Trials (Ovid SP), and ClinicalTrials.gov, for randomized controlled trials (RCTs) concerning SGLT2 inhibitors in patients with T1DM from inception to December 2023. Literature screening, quality assessment and data extraction were carried out independently by 2 researchers based on the inclusion and exclusion criteria, and statistical analysis was performed using Stata 15.1 software and R 4.1.3.ResultsNineteen clinical studies and one clinical trial were ultimately included. The study involved five different SGLT2 inhibitors. The incidence of DKA in dapagliflozin 5 mg (OR: 2.57, 95% CI: 1.04 to 6.33; P<0.00001), empagliflozin 10 mg (OR: 2.68, 95% CI: 1.11 to 6.49; P<0.00001), sogliflozin 200mg (OR: 4.04, 95% CI: 1.15 to14.18; P<0.00001) and sogliflozin 400mg (OR: 5.96, 95% CI: 2.06 to17.20; P<0.00001) were higher than for the placebo. According to the P scores, SGLT2 inhibitors triggered a lower incidence of DKA than did the placebo. Treatment with 300 mg canagliflozin had the lowest incidence of DKA (P score = 0.8563).ConclusionAccording to our study, 5 mg dapagliflozin,10 mg empagliflozin 200mg sogliflozin and 400mg sogliflozin resulted in DKA when adjunctive insulin was used to treat T1DM. Other SGLT2 inhibitors seem to be safe. However, SGLT2 inhibitors for treating T1DM are off label in China, and adverse reactions should be closely monitored during administration.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#loginpage, identifier CRD42023416227.